STRES AKADEMIK, RELIGIUSITAS DAN PSYCHOLOGICAL WELL-BEING PADA REMAJA DI PESANTREN RAUDHATUL IRFAN - Nita Rohayati; Aang Solahudin Anwar; Nursumiah Hajijah (Psychopedia Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2022)
During the Covid-19 pandemic, learning at the Raudhatul Irfan Islamic boarding school Karawang continue to be carried out face-to-face amid the threat of the Covid-19 pandemic, this causes problems on the psychological wellbeing of adolescents in Islamic boarding schools. The purpose of this research is to determine the relationship between academic stress and religiosity with Psychological wellbeing in the youth of Raudhatul Irfan Islamic Boarding School, Karawang. Study This method uses a correlational quantitative method, using three scales, the academic stress scale, religiosity scale and Psychological wellbeing scale. This research involving 42 students of the Raudhatul Irfan Islamic Boarding School, Karawang as a saturated sample in this study selected using a non-probability sampling technique, where all the research population into the sample. Data analysis techniques used in this study is multiple linear regression analysis test. The results of this study indicate that the value of Rsquare of 0.592; it means that 59.2% of the variation in psychological wellbeing is influenced by religiosity and stress, the remaining 40.8% is caused by other variables that are not measured in this research. The relationship between academic stress and religiosity with psychological wellbeing is known to have a significant relationship with a significance value of 0.000. Keywords: Psychological wellbeing, academic stress, religiousity, youth, Islamic boarding school Pada masa pandemic Covid-19, pembelajaran di pondok pesantren Raudhatul Irfan Karawang tetap dilakukan secara tatap muka ditengah ancaman pandemic Covid-19, hal ini menimbulkan permasalahan pada psychological wellbeing remaja di pondok pesantren. Tujuan penelitian ini adalah untuk mengetahui hubungan antara stress akademik dan religiusitas dengan Psychological wellbeing pada remaja Pondok Pesantren Raudhatul Irfan, Karawang. Penelitian ini menggunakan metode kuantitatif korelasional, dengan menggunakan tiga skala yaitu skala stress akademik, skala religiusitas dan skala Psychological wellbeing. Penelitian ini melibatkan 42 orang santri Pondok Pesantren Raudhatul Irfan, Karawang sebagai sampel jenuh dalam penelitian ini yang dipilih menggunakan teknik non probability sampling, dimana semua populasi penelitian menjadi sampel. Teknik analisis data yang digunakan dalam penelitian ini ialah uji analisis regresi linier berganda. Hasil penelitian ini menunjukkan bahwa nilai Rsquare sebesar 0,592; artinya sebesar 59,2% variasi pada psychological wellbeing dipengaruhi oleh religiusitas dan stres, sisanya sebesar 40,8% disebabkan oleh variabel lain yang tidak diukur dalam penelitian ini. Hubungan antara stres akademik dan religiusitas dengan psychological wellbeing diketahui memiliki hubungan yang signifikan dengan nilai signifikansi sebesar 0,000. Kata Kunci: Psychological wellbeing, stres akademik, religiusitas, remaja, pondok pesantren